2015
DOI: 10.1111/jphp.12442
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on phytochemical and pharmacological aspects of Elaeagnus angustifolia L.

Abstract: Objective Elaeagnus angustifolia L., commonly known as oleaster or Russian olive, is used worldwide as a traditional natural remedy or nutritional agent for the management of a wide range of illnesses. The aim of the present study is to comprehensively review the ethnopharmacological uses, biological activities and phytochemistry of E. angustifolia. Key findings Modern scientific investigations suggest that the plant possesses a broad spectrum of pharmacological and therapeutic effects, including antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 42 publications
1
46
0
1
Order By: Relevance
“…Plants belonging to this genus are famous for its medical benefits. Recent pharmacological studies have shown that E. angustifolia L. has anti-inflammatory, antimicrobial, antioxidant, antitumor, and cardiovascular effect [5]. A large number of phytochemical components have been derived from Russian olive and made this plant a source of flavonoids, alkaloids, saponin ,terpens and complicated sterols and sterols [6] as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Plants belonging to this genus are famous for its medical benefits. Recent pharmacological studies have shown that E. angustifolia L. has anti-inflammatory, antimicrobial, antioxidant, antitumor, and cardiovascular effect [5]. A large number of phytochemical components have been derived from Russian olive and made this plant a source of flavonoids, alkaloids, saponin ,terpens and complicated sterols and sterols [6] as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…7 Some of them were proven to exhibit anti-inflammatory, 1,8 muscle relaxant activity, 9 anti-ulcerogenic, 10 antimicrobial, [11][12][13][14] antinociceptive, 15,16 antitumor, 17,18 and antioxidant effects. 11,12,14,[19][20][21] Likewise, the whole fruit and medulla powder of E. angustifolia showed positive effect in improving pain, stiffness and physical function in women with osteoarthritis of the knee. 22,23 In Azarbaijan province folk medicine, the fruit and flower preparations have been used for healing jaundice, asthma, flatulence, vomiting and nausea.…”
Section: Introductionmentioning
confidence: 99%
“…24 Phytochemical studies on different extracts from fruits and flowers of E. angustifolia indicated the presence of polysaccharides, flavonoids, coumarins, phenolcarboxylic acids, amino acids, saponins, carotenoids, vitamins, and tannins as secondary metabolites. 12,13,25 Besides mentioned secondary metabolites, this plant also contains volatile oils that may be useful as a source of nutrition or pharmaceutical compounds. [26][27][28] To the best of our knowledge, the essential oil composition of the Iranian E. angustifolia has not been investigated; therefore, based on the prevalent food and medicinal uses of this plant, the present study was conducted to analyze the chemical composition of the essential oils hydrodistilled from the leaves and flowers of E. angustifolia as well as their general toxicity and radical scavenging activities.…”
Section: Introductionmentioning
confidence: 99%
“…In another plant endemic to Georgia, P. spinosa L., the amount of phenols again differed according to the area of cultivation and ranged from 331.0 mg to 114.9 mg/100 g. Antioxidant activity was somewhere around 25.11 mg. As for Georgian tangerines, the total amount of phenols varied between 0.364 mg and 0.474 mg/ml (in juice). The highest value radical scavenging activity among the samples was found in the tangerines Tiaxara Unshiu (80.05 mg) and Iwasaki (74.45 mg), with lower activities in samples of Mukoiyama and Clemenules, that is, 79.9-191.72 mg (Figure 2) [44,45].…”
Section: Antioxidant Activity Of Plant Extractsmentioning
confidence: 96%